Welfare state stabilization of employment careers: Unenployement benefits and job histories in the United States and West Germany - Markus Gangl (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
Economic job search theory offers two complementary predictions about the effects of unemployment benefits on job search outcomes among unemployed workers. By raising workers' reservation wages, unemployment benefits should contribute to both prolonged spell duration and improved post-unemployment job quality. In contrast to many previous empirical studies that have addressed the negative benefit effect on duration only, the current paper jointly addresses the causal effect of unemployment benefits on both unemployment duration and post-unemployment job quality. Based on discrete-time event history methods and U.S. and German panel data for the 1980s and 1990s, the paper establishes empirical support for both types of benefit effects in both countries. Hence, the effect of unemployment benefits on employment careers is more appropriately described as career stabilization induced by welfare state provision of job search resources. Against some prolongation of unemployment spells, unemployment benefits effectively enable workers to maintain previously accumulated human capital by fostering adequate reemployment in terms of earnings, occupations, or job duration. Consistent with this view, unemployment benefits turn out as particularly effective in preventing severe losses in postunemployment job quality, but also in terms of maintaining job qua lity among highskill workers. Through these effects of benefits on job histories, cross-national differences in welfare state generosity also assume an important role in explaining U.S.-German differences in terms of unemployment dynamics. – – Die ökonomische Suchtheorie macht zwei komplementäre Vorhersagen über die Einflüsse auf die Dynamik von Arbeitslosigkeit, die aus den Ansprüchen an die Arbeitslosenversicherung erwachsen. Wenn die Anspruchslöhne bei Arbeitnehmern angehoben werden, ist davon auszugehen, daß die daraus erwachsenden Ansprüche an die Arbeitslosenversicherung zu einer verlängerten Dauer der Arbeitslosigkeit und zu einer besseren Qualität der anschließenden Beschäftigung beitragen. Im Gegensatz zu vielen bisherigen empirischen Studien, die nur den negativen Effekt der Dauer der Arbeitslosigkeit betrachten, wird in diese Analyse der kausale Zusammenhang der Ansprüche an die Arbeitslosenversicherung sowohl auf die Dauer der Arbeitslosigkeit als auch auf die Qualität der an die Arbeitslosigkeit anschließenden Beschäftigung einbezogen. Auf der Basis ereignisanalytischer Modellschätzungen und amerikanischer bzw. deutscher Paneldaten für die 80er und 90er Jahre werden beide Effekte, die durch die Ansprüche an die Arbeitslosenversicherung ausgelöst werden, empirisch nachgewiesen. Der Effekt, den diese Ansprüche auf den weiteren Beschäftigungsverlauf haben, lässt sich angemessener beschreiben als die Stabilisierung von Erwerbsverläufen, erzielt durch wohlfahrtsstaatliche Transferleistungen zugunsten einer Stärkung der Ressourcen bei der Suche nach einer neuen Beschäftigung. Trotz einer gewissen Verlängerung der Dauer von Arbeitslosigkeit fördern die Unterstützungszahlungen während der Arbeitslosigkeit die Arbeitnehmer eindeutig bei der Erhaltung früher erworbenen Humankapitals, indem sie eine adäquate (bzgl. Einkommen, Tätigkeiten, Beschäftigungsdauer) Wiederbeschäftigung begünstigen.
Keywords: 330; Erwerbsverlauf; Arbeitslosigkeit; Arbeitsuche; Arbeitslosenversicherung; Qualifikation; Schätzung; Vergleich; Deutschland; USA